SPECIFICS OF SOYBEAN SEED PRODUCTION AND PROCESSING IN 2019 - Kostić, Miladin (Journal on Processing and Energy in Agriculture, 2020)
The soybean harvest in 2019 began at the end of August. The quality of the natural seed was very good. The moisture content of the harvested seeds ranged from 7.1% to 14.1%. Thanks to this humidity, there was no need to dry the seeds, which is very important given the fact that drying soybeans can reduce the quality. Seed germination ranged between 82% and 96%. It should be noted that 97% of seeds were harvested with germination greater than 85% while about 65% of seeds had germination above 90%. The weight of 1000 grains averaged about 160g. Soybean seed processing started on time and without major problems. The purity of the processed seed was on average 99.4%. Of the total amount of processed seeds, about 72% of seeds had germination greater than 85%. The achieved seed quality was better compared to 2018.
Keywords: soybean, production, harvest, seed reception, processing